Mitigating selective exposure to information by matching intervention messages to intrapersonal and interpersonal motivations - Banks, Lane Matthew (My University, 2025)
Across two studies, this dissertation aimed to mitigate selective exposure to information. Selective exposure (i.e., people not being willing to be exposed to counterattitudinal opinions and information) is problematic because optimal decisions and interpersonal interactions require unbiased exposure to information (Jang, 2014; Johnston, 1996; Pinkley et al., 1995). Selective exposure is motivated by defense, accuracy, or impression management concerns (Hart et al., 2009; Hart et al., 2020; Moore et al., 2023). Study 1 targeted the intrapersonal motivations of selective exposure: defense (maintaining one’s current attitude, belief, behavior, or self-concept), and accuracy (having a correct attitude/decision/judgment) through the use of theory-informed intervention messages. Results found that message frames, using cognitive/logical arguments, and advocating to be unbiased, why it is good to consider the opposite, and why looking at counterattitudinal information can enhance one’s ability to defend their views (inoculation) mitigated selective exposure. However, the frames based on cognitive dissonance theory, that used emotional appeals, were not effective (cognitive dissonance, and self-affirmation). Study 2 investigated the interpersonal motivation of selective exposure: impression management. Results from Study 2 found that short intervention messages that told people they should be openminded, that they could be liked by being open-minded and be liked and influential by being open-minded were effective at mitigating selective exposure. Furthermore, Study 2 included the personality variable of self-monitoring (Snyder, 1974), but the hypotheses were not supported. Selective exposure to information interferes with making good decisions, being able to defend one’s views, and good interpersonal interactions. It is promising that the two research studies were able to identify message frames to persuade participants to be less selective to information.
Keywords: Selective exposure